Otitis Media Efusi: Etiologi, Patofisiologi, Patogenesis, Epidemiologi, Diagnosis, Tatalaksana, Komplikasi - Brigitta Shinta dewi; Angelica Philia Christy; Nabila Alsa Sagia; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Otitis media with effusion is a common problem faced by general practitioners, paediatricians and otolaryngologists. Otitis media with effusion (OME) is a common clinical condition associated with hearing loss in which there is fluid in the middle ear but no acute infection. Otitis media with effusion is more affected in children, where it can be found in 80% of preschool children. Otitis media with effusion can cause significant delays and damage to communication and skills as well as difficulties in behavior and education. This article reviews the definition, several available etiological theories, pathophysiology of otitis media with effusion in the human body, epidemiology or spread of the disease, clinical diagnosis or symptoms found, complications, and how to manage patients with otitis media with effusion. Patients with otitis media with effusion often experience chief complaints of reduced hearing and a feeling of blockage in the ears. In children due to reduced hearing can cause speech disorders as well. To ensure that the patient really has otitis media with effusion, otoscopy, audiometry, and tympanometry can be done. Most otitis media with effusion can heal spontaneously, but there are several treatments that can be done, for example by using steroids, decongestants, histamine, or by decongesting. If the otitis media with effusion is not immediately given proper management, several complications will occur such as speech delays in children, changes in the structure of the ear, permanent hearing loss, and also tympanosclerosis